Urocanic acid enhances IL-10 production in activated CD4+ T cells - Holán, V; Kuffová, L; Zajícová, A; Krulová, M; Filipec, M; Holler, P; Jancárek, A (Journal of immunology (Baltimore, Md., 1998)
The immunosuppressive effects of UV radiation have been well documented. This suppression has been attributed to the action of the cis form of urocanic acid (UCA), a photoproduct of trans-UCA, a natural constituent of the skin. Here, we show that mouse spleen cells preincubated with cis-UCA have a diminished proliferative response to allogeneic cells in MLC and to stimulation with anti-CD3 mAb. Cells preincubated with cis-UCA also had a decreased ability to serve as APC and to stimulate the proliferation of allogeneic lymphocytes in MLC. Simultaneously, the production of IL-2 and IFN-gamma by cells preincubated with cis-UCA was decreased. However, IL-10 gene expression and IL-10 protein secretion by spleen cells stimulated in the presence of cis-UCA were significantly enhanced. The principal cell population displaying the cis-UCA-induced elevated production of IL-10 was CD4+ T cells, which were shown to be a direct target of cis-UCA action. This was also supported by the observation that production of IL-10 by stimulated splenic non-T cells or by macrophages was not altered by cis-UCA. The enhanced production of IL-10 by activated CD4+ T cells may represent a novel pathway of UVB radiation-induced, cis-UCA-mediated immunosuppression. We suggest that the elevated production of IL-10 by activated CD4+ T cells may account for the suppressor T cell phenomena described in UV-irradiated recipients.
Keywords: Gene Expression Regulation; T-Lymphocyte Subsets; Male; prezentace antigenu; slezina; Stereoisomerism; interleukin-10; Lymphocyte Activation; myši inbrední BALB C; mužské pohlaví; Interleukin-10; T-lymfocyty - podskupiny; aktivace lymfocytů; Mice, Inbred BALB C; Spleen; Adjuvants, Immunologic; stereoizomerie; CD4-Positive T-Lymphocytes; Animals; ženské pohlaví; Urocanic Acid; adjuvancia imunologická; zvířata; regulace genové exprese; kyselina urokanová; myši inbrední C57BL; myši; Mice, Inbred C57BL; Antigen Presentation; Mice; Female; CD4-pozitivní T-lymfocyty